Prevalence of Refractive Errors among Under Five Year Children Attending in a Tertiary Eye Care Center of Nepal - Thapa, Hari Bahadur; Bajracharya, Kabindra; Chaudhuri, Sirshendu; Agiwal, Varun; Judson, Katie; Bassett, Ken; Dev, Mahesh Kumar; Khadka, Saraswoti; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Refractive errors are common vision problems that occur when the shape of the eye does not properly bend or refract light to focus it on the retina. The objective of this research was to estimate the prevalence among children under-five years of age in Lumbini, Nepal. Methods A hospital-based observational study was conducted among children attending the Lumbini Eye Institute and Research Center. Participants were selected over three months using systematic random sampling. Ophthalmic examination with retinoscopy (dry and wet) was used to determine refractive errors. The proportion of children with spherical equivalent myopia ≤-0.50 diopter (D), SE hyperopia ≥+2.00 D and SE astigmatism >0.5 in both eyes were calculated. Prevalence of myopia, hyperopia and astigmatism was reported by age, gender and religion. Results Among 1,561 recruited children, the prevalence of refractive errors was 15.4% (n=240, 95% CI: 13.6% to 17.3%). The prevalence was significantly higher among older children (3 to 5 years) than the younger children (OR: 4.7; 95% CI: 1.7 to 13.1). Myopia was the most common condition (n=211, 13.5%, 95% CI: 11.9% to 15.3%). Myopia and astigmatism were significantly higher among children 3 to 5 years (22.1% and 5.56% respectively). Hyperopia prevalence was significantly higher among infants (3.3%). Conclusions The prevalence of refractive errors increased with age that was relatively high among infants and young children.